The Effect of Organizational Commitment and Compensation On The Performance of BPN Office Employees, West Aceh Regency - Wirda Fitria (Ridwan Institute, 2021)
This study aims to analyze the effect of organizational commitment and compensation on the performance of BPN office employees in West Aceh Regency. The objects studied were all employees at the BPN office in West Aceh district. Data collection techniques used quantitative methods in the form of questionnaires, interviews, observations, and document studies. This study uses primary data in the form of questionnaires or questionnaires distributed to all employees of the BPN office in West Aceh district, with a return rate of 97%. The data is then analyzed using multiple regression analysis to measure how much influence organizational commitment and compensation have on employee performance in the office West Aceh district BPN. The results of the study explain that organizational commitment has a positive effect on employee performance and compensation has a positive effect on employee performance. From the results of this study indicate that organizational commitment and compensation significantly influence employee performance in West Aceh district BPN office is at 69,27%.